s i m p l f y space t h e space f o l l w i n g space space e x p r e s s i o n s colon negative comma space open parentheses x plus y plus z close parentheses squared plus open parentheses x plus y minus z close parentheses squared space a n d space open parentheses 2 x plus p minus c close parentheses squared minus open parentheses 2 x minus p plus c close parentheses squared

Asked by kishor.kp14 | 26th Jun, 2019, 04:20: PM

Expert Answer:

We kow that,
(a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ac
1) (x + y + z)2 + (x + y - z)2
= x2 + y+ z2 + 2xy + 2yz + 2xz + x2 + y+ z2 + 2xy - 2yz - 2xz
= 2x2 + 2y+ 2z2 + 4xy
= 2(x2 + y+ z2 + 2xy)
2) (2x + p - c)2 - (2x - p + c)2
= (2x)2 + p2 + (-c)2 + 4xp - 2pc - 4xc - [(2x)2 + (-p)2 + c2 - 4xp - 2pc + 4xc)
= 4x2 + p2 + c2 + 4xp - 2pc - 4xc - 4x2 - p2 - c2 + 4xp + 2pc - 4xc
= 8xp - 8cx
= 8x(p - c)

Answered by Yasmeen Khan | 26th Jun, 2019, 05:31: PM